Identification of Insect Pests - Stephen H. Futch; Carl C. Childers; Clayton W. McCoy (EDIS)
This document is HS-893, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2002.